Pendidikan Agama Islam pada Remaja Keluarga Migran di Kabupaten Blora - Ika Miftakhul Hidayah; Agus Sutiyono; Nasirudin (EduInovasi: Journal of Basic Educational Studies, 2025)
The role of parents in educating children is very important, one of which is related to Islamic religious education. However, due to economic changes and high living needs, parents decided to become migrant workers. Leaving children in the care of substitute parents such as grandparents, uncles or aunts. It is known that children experience several periods, one of which is adolescence. Adolescence is a life transition both physically, psychologically and emotionally. This research aims to determine the implementation of Islamic religious education and the problems of Islamic religious education among teenagers from migrant families. This research uses descriptive qualitative methods, with data collection through observation and interviews. The research results show that Islamic religious education for teenagers from migrant families is carried out in three ways, first through formal education in the form of enrolling teenagers in religion-based schools, second, through informal education, such as instilling basic Islamic values, practicing worship and example. Third, through non-formal education in the form of reciting the Koran at the Al-Qur'an Education Park (TPQ) and the Koran Study House. The obstacles faced by parents' lack of involvement in religious education can result in children feeling a lack of love and attention, which has a negative impact on their emotional and spiritual development. Parenting is inconsistent and lacks discipline. It comes from the nature of grandparents and aunts who don't have the heart to scold their children and the nature of teenagers who think advice doesn't come from their biological parents.